Ocean Clean Energy: Optimizing the Use of Solar Panels to Increase Cooling Storage Efficiency for Fishermen in Sibolga Towards Sustainability and Climate Change Mitigation - Tulus Burhanuddin Sitorus; Yasmine Anggia Sari; Sarah Patumona Manalu; Hendrik Voice Sihombing; Ahmad Yunus Nasution; Mhd Azmy Vizzyansjah Lubis; Ananda El Shaddai Oktavia Siahaan; Muhammad Rizky Maulizar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve fishermen's welfare in Sibolga City by implementing more efficient technology. The main focus is enhancing fresh fish storage efficiency using refrigeration systems that utilize alternative energy. The activities involving faculty and students from the University of North Sumatra include raising awareness about alternative energy, promoting the use of solar panels, and installing them directly on fishing boats at Sibolga Harbor. The results of this initiative demonstrate increased awareness among fishermen about the importance of clean and sustainable energy. It is hoped that this will improve the quality of the catch, reduce operational costs, and contribute to local climate change mitigation efforts.